2006
DOI: 10.1111/j.1439-0426.2007.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Level of serum cortisol and Na+/K+ATP-ase activity of gills and kidneys in different acipenserids

Abstract: The levels of cortisol in blood serum and the Na + /K + activated ATP-ase activity in the homogenates of the gills and the kidneys were measured in different species of acipenserids in freshwater (control) and after different periods of acclimation to brackish water of 12.5-12.7‰ salinity. Immature sturgeons (2+ years old) were used for the study: the sterlet Acipenser ruthenus L.-a freshwater species from the middle of the Volga River; the Siberian sturgeon from the Lena River A. baerii Brandt -a freshwater s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…In the earlier studies, we (Krayushkina et al, 2006) have observed a significant increase in blood cortisol under acclimation to a hyperosmotic environment (salinity 12.5‰) in a less euryhaline sturgeon spe cies-freshwater sterlet A. ruthenus, which acclimates to such environment as an osmoconformer, and Sibe rian sturgeon of the Lena River population A. baerii, which has a limited osmoregulatory capacity. Under these conditions, the cortisol concentration increases 4 fold in sterlet and 3 fold-in the Siberian sturgeon, as compared with the hormone level in fish from fresh water.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the earlier studies, we (Krayushkina et al, 2006) have observed a significant increase in blood cortisol under acclimation to a hyperosmotic environment (salinity 12.5‰) in a less euryhaline sturgeon spe cies-freshwater sterlet A. ruthenus, which acclimates to such environment as an osmoconformer, and Sibe rian sturgeon of the Lena River population A. baerii, which has a limited osmoregulatory capacity. Under these conditions, the cortisol concentration increases 4 fold in sterlet and 3 fold-in the Siberian sturgeon, as compared with the hormone level in fish from fresh water.…”
Section: Discussionmentioning
confidence: 81%
“…The euryhaline species of acipenserids (Acipens eridae) that perform regular migrations "river → sea → river" are capable of maintaining a relatively constant serum osmolality when the environmental salinity is changed (Krayushkina et al, 1973;Krayushkina, Moiseenko, 1977;Krayushkina, 1998Krayushkina, , 2006Krayush kina, Semenova 2006). In these sturgeon species, as well as in the euryhaline teleosts (Zaks and Sokolova, 1965;Krayushkina 1983;Krayushkina et al, 1995), hyperosmotic regulation changes to the hypoosmotic during their transition from the river into the sea and thus a relative stability of blood serum osmolarity in the new environment is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Since NKA is highly expressed in fish chloride cells, its activity at the gill level must be enhanced with increased chloride cell size and number. This occurs in teleosts (Evans 1993;Cataldi et al 1995;McCormick 1996;McKenzie et al 1999;Mancera and McCormick 2000) and in sturgeons such as the starred sturgeon, A. stellatus, and the green sturgeons, A. medirostris, where NKA activity increases due to FW to BW transfer (Krayushkina et al 2006;Allen et al 2009). For Persian sturgeon juveniles, chloride cell hyperplasia appears to be salinity dependent with a 1.3-fold increase in the number of chloride cells within 10 days of abrupt or gradual transfer to BW.…”
Section: Abrupt Gradualmentioning
confidence: 95%
“…In some species and notably salmonids, NKA activity increases during transfer from FW to hyperosmotic condition and is directly correlated to the increased functional activity of branchial chloride cells (Marshall and Bryson 1998;Krayushkina et al 2006). Despite similar response in some sturgeons, changes of NKA activity with salinity are species specific and may also change through development (age or body size) in sturgeons Rodriguez et al 2002;Martinez Alvarez et al 2005;Krayushkina et al 2006).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation